β-lactoglobulin-irinotecan inclusion complex as a new targeted nanocarrier for colorectal cancer cells - Nooshin Bijari; Sirous Ghobadi; Katayoun Derakhshandeh (Wolters Kluwer Medknow Publications, 2019)
Beta-lactoglobulin (β-LG) is a lipocalin family member whose general function appears to be solubilizing and transport of hydrophobic molecules. Some properties such as avalability, ease of purification, and peculiar resistance to acidic environments can make β-LG as a carrier for hydrophobic and acid labile drugs for oral administration. In this protein vehicle, drug could be protected in acidic environment of stomach and then released within the basic small intestine. In this study, the potential of β-LG as a nanocarrier for oral delivery of a potent agent in colorectal cancer treatment, irinotecan, was evaluated. The nanoparticle was prepared by the physical inclusion complex method. Size, drug loading, encapsulation efficiency, and in vitro drug release at various pH values were investigated. The optimum formulation showed a narrow size distribution with an average diameter of 139.86 ± 13.75 nm and drug loading about 84.33 ± 5.03%. Based on the results obtained from docking simulation of irinotecan-complex, there are two distinct binding sites in this nanocarrier. Cytotoxicity of this nanocarrier on the HT-29 cancer cell line and AGS was measured by MTT assay. The cytotoxicity experiment showed that the drug-loaded nanocarrier was more effective than free drug. The higher release percent of drug from the β-LG complex at pH 7.4 compared to pH 1.2 indicated that the proposed nanocarrier could be introduced as a suitable nanovehicle for labile drugs in acidic medium targeted for colorectal segment.